Parameters affecting LED photoreactor efficiency in a heterogeneous photo-Fenton process using iron mining residue as catalyst - Rojas-Mantilla, Hernan Dario [UNESP]; Ayala-Duran, Saidy Cristina [UNESP]; Pupo Nogueira, Raquel Fernandes [UNESP] (Taylor & Francis Inc, 2019)
In this article, a light-emitting diode (LED)-based photoreactor was designed and evaluated for degradation of the antibiotic sulfathiazole (STZ), using heterogeneous photo-Fenton process with an iron ore residue as catalyst. The effects of the type of magnetic stirrer bar, use of baffles, rotation speed, and type and intensity of irradiation source were evaluated. The results showed that the degradation of STZ was strongly influenced by rotation speed (1100 rpm) and that the use of an octagonal stirrer bar favoured high dispersion and greater contact of the catalyst with the reaction medium. Although the presence of baffles had little influence on STZ degradation, their use enabled good dispersion of the catalyst (due to axial flow) and eliminated the vortex formed at high stirring speeds. It was found that the iron mining residue could be activated by UV LEDs, visible light LEDs, and black light irradiation, with similar degradation efficiencies achieved. Using the LEDs, STZ concentrations below the detection limit were obtained after 40 min, with power consumption 38-fold (UV LEDs) and 22-fold (visible light LEDs) lower than required for black light irradiation. The results demonstrated the advantages of the use of LED devices as irradiation systems in heterogeneous photo-Fenton processes.
Keywords: Photoreactor; light-emitting diode; stirring system; baffles; sulfathiazole